A new proposed nomenclature for microhaplotypes. Issue 1 (December 2019) - Zhu, Jing; Long, Bing; Qu, Shengqiu; Yin, Lu; He, Wang; Mao, Jiong; Wang, Hui; Zhang, Lin; Jin, Bo; Chen, Dan; Liang, Weibo
Abstract: Microhaplotype marker is a new type of forensic genetic marker, and it is becoming more and more important with the development of massively parallel sequencing technology. Therefore, a unified and standardized nomenclature is required. Kenneth K. Kidd has proposed and published a nomenclature for microhaplotype markers. The nomenclature involves a root "MH" which is followed by chromosome numbers and unique characters established by the authors in their initial publication. Mh01kk001 is an example following this nomenclature system. Almost at the same time, our team proposed another similar nomenclature. After comparing it with Kidd' nomenclature, our team improved our nomenclature and proposed a supplement for the nomenclature of microhaplotype markers. It involves five parts: the root "MH", the chromosome number, the name of lab which published the loci initially, the individual numbers of the loci and the version number that defined by the cluster of SNPs, for example, mh01kk001A.